Does Open Guide Suture Technique Improve the Patency Rate in Submillimeter Rat Artery Anastomosis? - Mofikoya, B. O.; Ugburo, A. O.; Bankole, O. B. (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2014)
The anastomosis of sub-millimeter vessels is fraught with significant technical challenges even for the experienced microsurgeon. The supermicrosurgery era is increasing the demand for repair of very small vessels. Our study aims to ascertain whether the open guide suture technique provides a superior patency rate compared with conventional technique when anastomosing rat artery less than a millimeter.Anastomosis of transected rat femoral, superficial femoral and central tail arteries were done in 24 in bred albino rats. The external diameters ranged from 0.4 mm to 0.8 mm. The repair was assigned into the Open guide suture technique group or the conventional group (n=12 in each group). The duration of repair, grade of leakage, patency of the repair at 30 min were noted and compared between the groups.The patency rate was 92.7% in each group. There was no statistically significant difference between the 2 groups with respect to anastomotic times, grade of leakage external diameter and type of vessel repaired (p-values >0.05).It appears open guide suture technique simplifies repair but may not offer a better patency rate in rat arterial anastomosis under 1 mm when compared to the conventional technique.
Keywords: open; guide; suture; anastomosis; microsurgery